Reduced Graphene Oxide–Ag3PO4 Heterostructure: A Direct Z‐Scheme Photocatalyst for Augmented Photoreactivity and Stability. Issue 4 (8th January 2016) - Samal, Alaka; Das, D. P.; Nanda, K. K.; Mishra, B. K.; Das, J.; Dash, A.
Abstract: A visible light driven, direct Z‐scheme reduced graphene oxide–Ag3 PO4 (RGO–Ag3 PO4 ) heterostructure was synthesized by means of a simple one‐pot photoreduction route by varying the amount of RGO under visible light illumination. The reduction of graphene oxide (GO) and growth of Ag3 PO4 took place simultaneously. The effect of the amount of RGO on the textural properties and photocatalytic activity of the heterostructure was investigated under visible light illumination. Furthermore, total organic carbon (TOC) analysis confirmed 97.1 % mineralization of organic dyes over RGO–Ag3 PO4 in just five minutes under visible‐light illumination. The use of different quenchers in the photomineralization suggested the presence of hydroxyl radicals ( . OH), superoxide radicals ( . O2 − ), and holes (h + ), which play a significant role in the mineralization of organic dyes. In addition to that, clean hydrogen fuel generation was also observed with excellent reusability. The 4 RGO–Ag3 PO4 heterostructure has a high H2 evolution rate of 3690 μmol h −1 g −1, which is 6.15 times higher than that of RGO. Abstract : Photo finish : A direct Z‐scheme reduced graphene oxide (RGO)–Ag3 PO4 heterostructure photocatalyst was synthesized by means of a one‐pot photoreduction method with an average particle size of approximately 20–25 nm (see figure). The as‐synthesized heterostructure not only swiftly mineralized organic textile dyes, but was also able to generate up to 3690 μmol h −1 g −1 of H2 with excellent recyclability without co‐catalyst.